SPEECH BY HIS EXCELLENCY DANIEL T. ARAP MOI, C.G.H. DURING THE OFFICIAL OPENING OF THE 3RD ANNUAL KABARAK UNIVERSITY INTERNATIONAL RESEARCH CONFERENCE ON 16TH OCTOBER 2013 AT KABARAK UNIVERSITY SCHOOL OF LAW - MATEGET, MATEGET (My University, 2013)
I TAKE THIS OPPORTUNITY TO WELCOME YOU ALL TO THE THIRD ANNUAL KABARAK UNIVERSITY INTERNATIONAL CONFERENCE. I’M GLAD THAT THE THEME FOR THIS YEAR’S CONFERENCE FOCUSES ON APPLIED RESEARCH AND INNOVATION. THIS IS OF GREAT NEED FOR AFRICA AND DEVELOPING COUNTRIES TODAY. 2 TIME HAS COME FOR AFRICA TO TAKE THE LEAD IN ECONOMIC DEVELOPMENT AND INNOVATION. AFRICAN CONTINENT MUST SHIFT ITS FOCUS FROM BASIC TO APPLIED RESEARCH IF IT IS TO TRANSFORM FROM POVERTY TO PROSPERITY. AFRICA IS LAGGING BEHIND OTHER CONTINENTS IN INNOVATION BECAUSE OF OVEREMPHASIS ON BASIC RESEARCH CONDUCTED SOLELY FOR INFORMATION GATHERING AND BUILDING ON 3 EXISTING KNOWLEDGE INSTEAD OF APPLIED RESEARCH, WHICH IS GEARED TOWARDS THE RESOLUTION OF A PARTICULAR QUESTION OR PROBLEM. THIS CONTINENT DOES NOT NEED RESEARCH TO LEARN ABOUT HOW SOMETHING WORKS, WE NEED STUDIES INTO THE ORIGINS OF THE PROBLEMS AND RECOMMENDATIONS FOR REALISTIC SOLUTIONS. AFRICAN NATIONS NEED INNOVATIVE POLICIES AND INSTITUTIONS THAT 4 ARE RELEVANT, INCLUDING TECHNOLOGICAL CAPABILITY, TECHNICAL PROGRESS AND COMMITMENT TO INNOVATION. A SPIRIT OF INFORMATION-SHARING AMONG NATIONS AND NATIONAL AGENCIES IS ALSO LACKING, WHICH COULD INFLUENCE INNOVATIVE BEHAVIOUR AND PERFORMANCE. I’M GLAD THAT A RESEARCH CONFERENCE LIKE 5 6 THIS PROVIDES A PLATFORM FOR INFORMATION SHARING AND NETWORKING AMONG SCHOLARS AND RESEARCHERS. I WOULD LIKE TO CALL UPON THE PRIVATE AND THE GOVERNMENT SECTORS TO WORK TOGETHER WITH UNIVERSITIES AND TAKE A LEAD IN APPLIED RESEARCH WITH EMPHASIS IN INNOVATION. I’M IMPRESSED BY THE LARGE TURN OUT OF RESEARCHERS AND PARTICIPANTS IN THIS YEARS CONFERENCE. KENYA AND AFRICA AND INDEED THE WORLD IS COUNTING ON YOU. MY ADVICE TO YOU ALL IS MAKE RESEARCH PART OF YOUR LIFE. 7
Keywords: H.E DANIEL TOROITICH ARAP MOI SPEECH